Educational empowerment in the field of high intellectual capacities. Myths and beliefs in the Primary Education teachers - Emilio López Parra; María Inés Martín García; Ascensión Palomares Ruiz (Universidad de La Rioja, 2019)
Students with high intellectual abilities have educational needs that for various reasons are not always adequately addressed. This research is defined in this complex situation and its purpose is to know what the perceptions of Primary Education teachers in relation to such important aspects as performance, social behaviours and skills, gender and the most appropriate educational response to meet their educational needs. It looks into these teachers' training, and the influence of this training in the presence of stereotypes and myths about high abilities. A mixed methodology is used, whose quantitative approach analyze the perceptions and beliefs of 343 teachers through a questionnaire and, from a qualitative perspective, it picks the preferences on the most effective educational response for these students through a structured interview on 6 primary education teachers. The results show that some of the most common myths and stereotypes about these students are still rooted, that there are still important deficiencies in the training level and that the educational response should be more individualized according to the needs of each student. This leads us to conclude that it is necessary to establish training programs for teachers, as a fundamental element to improve the academic and personal life of students with high intellectual abilities.